Padre Cícero Romão e o catolicismo popular no nordeste brasileiro : paradigma para ação pastoral da atualidade - Soares, Emiliano Dantas (2015)
This paper presents some of the life and work of Padre Cícero Romão Batista and some of the popular Catholicism scenarios in the Brazilian Northeast, seeking the maximum value the faith experiences of the northeastern backlands. Pe. Cícero Romão and his style of pastoring, form and animate the northeastern mass is indicated as a paradigm for today's ecclesial action. A Catholic priest since 1872, became a church model at the service of the less fortunate, without leaving aside what is proper to the Christian faith. After decades of his death, it remains a benchmark of life, service, charity and Christian faith for millions of Brazilians, and a challenge to the way of being church in our times.